Evolution and population structure of Salmonella enterica serovar Newport. - Sangal, V; Harbottle, H; Mazzoni, C; Helmuth, R; Guerra, B; Didelot, X; Paglietti, B; Rabsch, W; Brisse, S; Weill, F; Roumagnac, P; Achtman, M (2010)
Salmonellosis caused by Salmonella enterica serovar Newport is a major global public health concern, particularly because S. Newport isolates that are resistant to multiple drugs (MDR), including third-generation cephalosporins (MDR-AmpC phenotype), have been commonly isolated from food animals. We analyzed 384 S. Newport isolates from various sources by a multilocus sequence typing (MLST) scheme to study the evolution and population structure of the serovar. These were compared to the population structure of S. enterica serovars Enteritidis, Kentucky, Paratyphi B, and Typhimurium. Our S. Newport collection fell into three lineages, Newport-I, Newport-II, and Newport-III, each of which contained multiple sequence types (STs). Newport-I has only a few STs, unlike Newport-II or Newport-III, and has possibly emerged recently. Newport-I is more prevalent among humans in Europe than in North America, whereas Newport-II is preferentially associated with animals. Two STs of Newport-II encompassed all MDR-AmpC isolates, suggesting recent global spread after the acquisition of the bla(CMY-2) gene. In contrast, most Newport-III isolates were from humans in North America and were pansusceptible to antibiotics. Newport was intermediate in population structure to the other serovars, which varied from a single monophyletic lineage in S. Enteritidis or S. Typhimurium to four discrete lineages within S. Paratyphi B. Both mutation and homologous recombination are responsible for diversification within each of these lineages, but the relative frequencies differed with the lineage. We conclude that serovars of S. enterica provide a variety of different population structures.